2020
DOI: 10.3390/ijerph17072462
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infection Knowledge among Older Adults: Psychometrics and Test–Retest Reliability

Abstract: Sexually transmitted infections (STI) among older adults have dramatically increased in recent years, especially among those who are widowed and divorced. The purposes of this study were to: (1) identify STI-related knowledge among older adults; (2) report the psychometric properties of a tool commonly used to assess STI-related knowledge among younger populations using data from adults 65 years and older; and (3) determine test-retest reliability of the tool. Data were analyzed from 43 adults, aged 65–94 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“…Another study noted an increase in the use of condoms among older Black participants reporting multiple sexual partners [ 19 ], suggesting knowledge of how to prevent HIV and STIs. Yet a third study conducted primarily among a sample of older white adults found broadly low knowledge regarding transmission and acquisition risk of HIV and STIs [ 20 ]. While we did not specifically address knowledge or self-perceived risk of HIV/STIs in this study, we did assess prevention methods used by our sample of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Another study noted an increase in the use of condoms among older Black participants reporting multiple sexual partners [ 19 ], suggesting knowledge of how to prevent HIV and STIs. Yet a third study conducted primarily among a sample of older white adults found broadly low knowledge regarding transmission and acquisition risk of HIV and STIs [ 20 ]. While we did not specifically address knowledge or self-perceived risk of HIV/STIs in this study, we did assess prevention methods used by our sample of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…National surveillance data demonstrate that rates of primary and secondary syphilis have more than doubled for individuals in the 55 to 64 years and 65 years or older age groups over the period of 2015 to 2019 3 . Barriers, such as provider discomfort with asking older adults sexual health questions, and limited sexual health knowledge among older adults, may reduce screening and early detection of sexually transmitted infections in these individuals 28–30 . Among syphilis cases included in our analysis, the increasing reported prevalence of neurologic, ocular, and otic manifestations with age could be explained by factors, such as longer duration of unrecognized infection with T. pallidum , more frequent health care visits for other underlying comorbidities that increase opportunities for detection, or better access to health care among those eligible for Medicare.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth noting that the number of seniors who acquire sexually transmitted infections has increased in several countries around the world, especially those in development, due to lack of knowledge, unsafe sexual practice and the taboo that encourages social prejudice related to sexuality in the elderly, which ultimately make this population vulnerable to diseases [31].…”
Section: Discussionmentioning
confidence: 99%